2019
DOI: 10.1016/j.ijpx.2019.100027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism investigation of ethosomes transdermal permeation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 57 publications
(56 reference statements)
0
44
0
Order By: Relevance
“…As suggested by other authors, SLN appear less efficient to promote drug permeation as compared to ETHO. Indeed, many studies have suggested that SLN can exert an occlusive effect [ 56 , 57 , 58 ], promoting the formation of a drug depot in or on the stratum corneum , while other studies have demonstrated that elastic ETHO can penetrate the stratum corneum through the intercellular spaces and release the loaded drug [ 25 , 30 , 31 , 32 ]. In this respect, the transdermal effect of ETHO-CA promotes a more intense and prolonged antioxidant activity of CA with respect to SLN-CA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by other authors, SLN appear less efficient to promote drug permeation as compared to ETHO. Indeed, many studies have suggested that SLN can exert an occlusive effect [ 56 , 57 , 58 ], promoting the formation of a drug depot in or on the stratum corneum , while other studies have demonstrated that elastic ETHO can penetrate the stratum corneum through the intercellular spaces and release the loaded drug [ 25 , 30 , 31 , 32 ]. In this respect, the transdermal effect of ETHO-CA promotes a more intense and prolonged antioxidant activity of CA with respect to SLN-CA.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, many studies have evidenced the transdermal effect of ETHO, allowing the deep penetration of drugs through the skin strata [ 25 , 30 , 31 ]. In line with this, ethanol is supposed to disorganize the stratum corneum barrier, opening spaces through which the soft and malleable ETHO vesicles can pass, as indicated by the presence of intact ETHO in the epidermis [ 25 , 32 ]. Different nanosystems have been investigated as carriers for phenolic compounds; however, to the best of our knowledge, the influence of the nanosystem type on the antioxidant behavior and transdermal potential of the phenolic compound has not been yet investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 0.5% HAL-ES-mediated aPDT further significantly inhibited the activity and growth of C. albicans biofilm within 48 h, mainly due to the effective reduction of biofilm hyphae. This can be because ES, as a nanocarrier, contains a high concentration of ethanol and is of reduced size, allowing the drug to effectively penetrate the structure of biofilm and cell membranes ( Zhang et al, 2014 ; Niu et al, 2019 ). Hyphae play a pivotal role in the spatial structure and compressive strength of biofilms ( Paramonova et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are formed from phospholipids, water and high concentrations of alcohols (ethyl alcohol or isopropanol) [ 98 ] that provide elastic properties to the vesicles as well as increase the encapsulation efficiency of lipophilic molecules, especially compared to conventional liposomes. Halan et al [ 99 ] prepared ethosomes incorporating caffeic acid for transdermal delivery. The study revealed that the encapsulation efficiency of caffeic acid was greater compared to other systems described in the literature and that caffeic acid was stabilized, maintaining its antioxidant potential for prolonged time.…”
Section: Organic-based Delivery Systemsmentioning
confidence: 99%